Pancreatic main-duct involvement in branch-duct IPMNs: an underestimated risk - Fritz, Stefan; Klauß, Miriam; Bergmann, Frank; Strobel, Oliver; Schneider, Lutz; Werner, Jens; Hackert, Thilo; Büchler, Markus W. (Annals of surgery, 2014)
OBJECTIVES: This study aimed to analyze a large single-center population of resected intraductal papillary mucinous neoplasms (IPMN) of the pancreas with respect to risk factors of malignant transformation. - BACKGROUND: There is international consensus that main-duct (MD) as well as mixed-type IPMNs should be treated surgically due to a high risk of malignancy. In contrast, there is an ongoing controversy about surgery of branch-duct type IPMN (BD-IPMN). - METHODS: All consecutive patients who underwent surgery for IPMN between January 2004 and December 2012 were included. Clinical characteristics and preoperative imaging were correlated with histopathological features. - RESULTS: A total of 512 patients underwent pancreatic surgery and had a histological proof of IPMN. According to preoperative imaging, 74 patients had MD-IPMN (14%), 205 mixed-type (40%), and 233 suspected BD-IPMN (46%). On histopathology, 162 of 512 patients revealed low-grade, 105 moderate, and 52 high-grade dysplasia. One hundred ninety-three IPMN patients (38%) suffered from invasive carcinoma. Among invasive IPMNs, the majority (58%) were mixed-type lesions according to preoperative imaging. Of 141 Sendai negative BD-IPMNs, a malignancy rate of 18% (high-grade dysplasia and invasive carcinoma) was found. Most interesting, 29% of suspected BD-IPMNs (67/233) revealed histological involvement of the main pancreatic duct not evident in preoperative imaging. - CONCLUSIONS: All subtypes of IPMNs display a relevant risk for malignant transformation. By abdominal imaging, many IPMNs are misclassified as BD-IPMNs but reveal mixed-type lesions in histopathology. Because currently available preoperative diagnostics are not sufficient to reliably diagnose BD-IPMNs, surgical resection for suspected small branch-duct IPMN should be considered in patients fit for surgery.
Gesehen am 13.01.2021